A historical overview of the curricular guidelines for teacher training and mathematics teaching in Brazil: from the First Letters Law to LDB/96 (2022)
In this article, we share the results of a research that shows the implications of the implementation of curricular guidelines for teacher education and mathematics teaching in the main curriculum reforms in Brazil. The research was bibliographic and documental. The results show the characterization of the repercussions that occurred from the implementation of the Law of First Letters (and the Normal Schools), the Francisco Campos Reforms, the Gustavo Capanema Reform, the 1961 Law of Directives and Bases of National Education, the 1971 Law of Directives and Bases of National Education, and the 1996 Law of Directives and Bases of National Education.